Validitas Buku Ensiklopedia Burung Air di Hutan Pantai Tabanio dalam Melatih Keterampilan Berpikir Kritis - Muhammad Zidane; Muhammad Zaini; Kaspul Kaspul (Mathematics Education Study Program, 2025)
In the context of 21st-century education, critical thinking skills are becoming one of the four essential skills (4Cs) that students must possess. One method for developing these skills is through the use of appropriate teaching materials, such as encyclopedias. This study aims to examine the content validity of an encyclopedia focused on waterbirds in the Mangrove area ofanio Village as a tool training critical thinking skills in students. This research is limited to the content validation of the encyclopedia and uses the Educational Design Research (EDR) method. research object is the developed encyclopedia, while the research subjects three experts serve as. The validation results show the encyclopedia is included in the valid category with an average score of 3.53, thus it be appropriate as an alternative learning source for training critical thinking skills.